Factors affecting profitability: Evidence from Indonesia and Malaysia - Joshua Syukran Taruli; Rosinta Ria Panggabean (Prosiding Industrial Research Workshop and National Seminar, 2019)
This study was conducted to examine factors affecting the profitability of companies listed on Indonesia Stock Exchange and Bursa Malaysia. The factors tested were activity, liquidity and corporate governance. Methodology: The population of this study includes all property and real estate companies listed on Indonesia Stock Exchange and Bursa Malaysia within the period of 2013-2017. The research used purposive sampling method and obtained 37 sample companies. Multiple regression analysis method was used in this research. The results show that in Indonesian companies, activity and liquidity have significant effect on ROE, while Corporate Governance have no effect on Return on Equity. The results in Bursa Malaysia show that activity and Corporate Governance (Board Independence) have a positive and significant effect on Return on Equity. Meanwhile, Liquidity and Board Size have no effect on ROE. Value: This study developed previous research by adding corporate governance variables.